2022
DOI: 10.1088/1361-648x/ac5310
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress of heterostructures based on two dimensional materials and wide bandgap semiconductors

Abstract: Recent progress in the synthesis and assembly of two-dimensional (2D) materials has laid the foundation for various applications of atomically thin layer films. These 2D materials possess rich and diverse properties such as layer-dependent band gaps, interesting spin degrees of freedom, and variable crystal structures. They exhibit broad application prospects in micro-nano devices. In the meantime, the wide bandgap semiconductors (WBS) with an elevated breakdown voltage, high mobility, and high thermal conduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 150 publications
(272 reference statements)
0
13
0
Order By: Relevance
“…The rise of 2D materials has garnered considerable interest caused of their planar structures, free of dangling bonds, layer‐dependent electronic band structure, excellent mechanical flexibility, outperformed electrical, optical, thermoelectric, and electrochemical characteristics, and compatibility with other materials. [ 1–13 ] In the past few years, 2D materials have been employed for the state‐of‐the‐art electronic and optoelectronic devices. [ 14–18 ] Among the broad list of reported 2D materials, graphene is the most‐prominent material due to its remarkably high carrier mobility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rise of 2D materials has garnered considerable interest caused of their planar structures, free of dangling bonds, layer‐dependent electronic band structure, excellent mechanical flexibility, outperformed electrical, optical, thermoelectric, and electrochemical characteristics, and compatibility with other materials. [ 1–13 ] In the past few years, 2D materials have been employed for the state‐of‐the‐art electronic and optoelectronic devices. [ 14–18 ] Among the broad list of reported 2D materials, graphene is the most‐prominent material due to its remarkably high carrier mobility.…”
Section: Introductionmentioning
confidence: 99%
“…flexibility, outperformed electrical, optical, thermoelectric, and electrochemical characteristics, and compatibility with other materials. [1][2][3][4][5][6][7][8][9][10][11][12][13] In the past few years, 2D materials have been employed for the state-of-the-art electronic and optoelectronic devices. [14][15][16][17][18] Among the broad list of reported 2D materials, graphene is the most-prominent material due to its remarkably high carrier mobility.…”
mentioning
confidence: 99%
“…Water splitting requires stable photocatalysts having high optical adsorption and low reaction barriers. Recent progress on photocatalysts has been reported by researchers [51,52]. Ju et al found that the WSSe monolayer shows good photocatalysis properties from DFT simulations.…”
Section: Photocatalysts For Hydrogen Evolutionmentioning
confidence: 99%
“…24,36,37 Gallium nitride (GaN), one of the third-generation wide bandgap semiconductors, has received much attention owing to its high breakdown electric fields, high thermal conductivity, good chemical stability and strong irradiation resistance (related to its high internal and external quantum efficiencies). 38,39 Therefore, GaN has broad application prospects in the fields of optoelectronics, highpower devices and high-frequency microwave devices. Recently, SEM has been utilised to characterise the spatial distribution of dopants in p-i-n GaN specimens by establishing a correlation between the SE intensity and the doping contrast.…”
Section: Introductionmentioning
confidence: 99%